Fungsi Ritual Tari Ngrengkau pada Masyarakat Dayak Benuak di Kalimantan Timur - Muhammad Muttaqin (Institut Seni Indonesia Surakarta, 2010)
The performance of the Ngerangkau dance in the Kwangkai ritual is a re-actualization of the mystic relationship between the Dayak Benuaq community and the spirits of their deceased ancestors. This community becomes afraid if this ritual is not performed, since they believe that by performing the Ngrengkau dance ritual, they will be protected and kept away from any danger. For this reason, the ritual has been preserved, due to its close connection with various concerns of the Dayak Benuaq community, such as its function in escorting the souls of the dead to heaven, entertaining the spirits, keeping away evil spirits, ensuring fertility, and honouring the ancestors of the local community, in addition to other functions in the life of the community. Keywords : Ngrengkau dance, function, and ritual.